Ir(triNHC)-Catalyzed Upcycling of Waste PET for Lactic Acid Production with Sustainable Isolation via Bipolar Membrane Electrodialysis - Lee, Mi hyun; Kim, Ji Hoon; Hwang, Young Kyu; Jang, Hye Young (Angewandte Chemie - International Edition, 2024)
For the upcycling of waste polyethylene terephthalate (PET), encompassing both colored and fabric PET materials, we investigated the Ir(triNHC)-catalyzed dehydrogenative coupling of PET and methanol, leading to the production of sodium lactate with good yields. We proposed a sustainable method for isolating lactic acid from the catalytic reaction mixture of sodium lactate and regenerating the base using bipolar membrane electrodialysis (BMED). This isolation method demonstrated high effectiveness, achieving isolation of lactic acid while maintaining economic feasibility at $ 0.10 per kg of lactic acid, and enabling sustainable NaOH regeneration with complete resource circulation. We assessed the recyclability of the catalyst and elucidated the mechanism involving base-mediated depolymerization and catalyst-promoted dehydrogenation, highlighting the importance of triNHC ligands in enhancing catalytic activity.
Keywords: Bipolar membrane Electrodialysis; Catalytic reactions; Dehydrogenative coupling; Lactic acid production; Reaction mixture; Sodium lactate; Sustainable isolation; Upcycling; Waste polyethylene terephthalates; ]+ catalyst; dehydrogenative coupling; lactic acid; sustainable isolation; upcycling; waste PET